Severity of old world cutaneous leishmaniasis is influenced by previous exposure to sandfly bites in Saudi Arabia. - Karina Mondragon-Shem; Waleed S Al-Salem; Louise Kelly-Hope; Maha Abdeladhim; Mohammed H Al-Zahrani; Jesus G Valenzuela; Alvaro Acosta-Serrano (Public Library of Science (PLoS), 2015)
BACKGROUND:The sandfly Phlebotomus papatasi is the vector of Leishmania major, the main causative agent of Old World cutaneous leishmaniasis (CL) in Saudi Arabia. Sandflies inject saliva while feeding and the salivary protein PpSP32 was previously shown to be a biomarker for bite exposure. Here we used recombinant PpSP32 to evaluate human exposure to Ph. papatasi bites, and study the association between antibody response to saliva and CL in endemic areas in Saudi Arabia. METHODOLOGY/PRINCIPAL FINDINGS:In this observational study, anti-PpSP32 antibodies, as indicators of exposure to sandfly bites, were measured in sera from healthy individuals and patients from endemic regions in Saudi Arabia with active and cured CL. Ph. papatasi was identified as the primary CL vector in the study area. Anti-PpSP32 antibody levels were significantly higher in CL patients presenting active infections from all geographical regions compared to CL cured and healthy individuals. Furthermore, higher anti-PpSP32 antibody levels correlated with the prevalence and type of CL lesions (nodular vs. papular) observed in patients, especially non-local construction workers. CONCLUSIONS:Our findings suggest a possible correlation between the type of immunity generated by the exposure to sandfly bites and disease outcome.